1998
DOI: 10.1016/s0022-2275(20)32465-2
|View full text |Cite
|
Sign up to set email alerts
|

Estradiol as an antioxidant: incompatible with its physiological concentrations and function

Abstract: Estradiol has been documented to inhibit the oxidation of low density lipoprotein (LDL). We show that physiological concentrations of estradiol do not inhibit the oxidation of LDL by copper. LDL samples isolated from a ) premenopausal and postmenopausal women and from b ) women at different time periods during their menstrual cycle, who differ vastly in plasma estradiol levels, were also oxidized at the same rates by copper. In contrast, LDL samples isolated from c ) women who were hyperstimulated during in vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 95 publications
(9 citation statements)
references
References 56 publications
(63 reference statements)
0
9
0
Order By: Relevance
“…30 Furthermore, it has been suggested that in fact, at physiological concentrations, oestrogens might bear pro-oxidant activity through myeloperoxidase activation. 31 In this way, we suggest that IVF treatment could induce a rise in plasma oxidation that would lead to an increase in oxidation of the membrane phospholipids and the consequent triggering of anti-PL antibody production. These antibodies have been correlated with a reduction in PON activity in patients with APS, 24 enhancing in this way the oxidation levels of plasma that in turn would further increase the oxidation of membrane phospholipids, hence perpetuating this condition.…”
Section: Discussionmentioning
confidence: 82%
“…30 Furthermore, it has been suggested that in fact, at physiological concentrations, oestrogens might bear pro-oxidant activity through myeloperoxidase activation. 31 In this way, we suggest that IVF treatment could induce a rise in plasma oxidation that would lead to an increase in oxidation of the membrane phospholipids and the consequent triggering of anti-PL antibody production. These antibodies have been correlated with a reduction in PON activity in patients with APS, 24 enhancing in this way the oxidation levels of plasma that in turn would further increase the oxidation of membrane phospholipids, hence perpetuating this condition.…”
Section: Discussionmentioning
confidence: 82%
“…Studies utilizing physiological doses of estradiol are conflicting. Recent work by Santanam et al (41) suggested that at physiological concentrations, estradiol did not function as an antioxidant and protect LDL from Cu ϩ2 -mediated oxidation. Conversely, work by Shwaery and colleagues (14) showed that physiological levels of estradiol associated with LDL and also, incubation of estradiol with LDL in the presence of plasma protected against aqueous peroxyl radical-mediated oxidation.…”
Section: Discussionmentioning
confidence: 97%
“…Recently, the induction of heme oxygenase (which would generate potent antioxidants such as bilirubin and biliveridin) (133)(134)(135), catalase (136) (O. Meilhac, unpublished observations) and glutathione (137,138) by vascular cells under oxidative stress has been described. These findings raise an inescapable conclusion that a mild oxidative stress might itself lead to the body's antioxidant defense, a conclusion that might be supported by circumstantial studies from in vivo studies (116,139,140). These studies indicated that beginning exercisers suffer an oxidative stress whereas conditioned exercisers are well protected, as determined by the susceptibility of isolated LDL to oxidation (140).…”
Section: Can Prooxidants Be Beneficial?mentioning
confidence: 89%
“…More importantly, whether the observed effects could be attributed to pro-or antioxidant effects could not be established. The probability of a phenolic antioxidant to become a prooxidant is well illustrated by estradiol (116). Not only does it have the ability to become a prooxidant in the presence of peroxidases, its increased presence is also associated with an increased neutrophil activation and release of myeloperoxidase (MPO) (117).…”
Section: Antioxidants As Prooxidantsmentioning
confidence: 99%
See 1 more Smart Citation